Antimicrobial stewardship capacity and manpower needs in the Asia Pacific. (March 2021) - Lee, Tau Hong; Lye, David C.; Chung, Doo Ryeon; Thamlikitkul, Visanu; Lu, Min; Wong, Andrew TY; Hsueh, Po-Ren; Wang, Hui; Cooper, Celia; Wong, Joshua GX; Shimono, Nobuyuki; Pham, Van Hung; et al.
Highlights: One hundred and thirty-nine participants in 16 countries/regions from the Asia-Pacific completed this survey on antimicrobial stewardship capacity. Although three quarters of respondents worked in large hospitals, only about 15% reported having more than 10 infectious diseases physicians. Participants from 7 countries reported that antimicrobials can be obtained without prescriptions. Pre-authorisation of antimicrobials, and prospective audit and feedback were reported by approximately 80% of respondents. Culture guided de-escalation were reported only in 24% of respondents. Abstract: Objectives: Antimicrobial stewardship is a strategy to combat antimicrobial resistance in hospitals. Given the burden and impact of antimicrobial resistance in the Asia Pacific, it is important to document capacity and gaps in antimicrobial stewardship programmes (ASP). We aimed to understand existing capacities and practices, and define the resources needed to establish antimicrobial stewardship where it is lacking. Methods: An anonymous online survey, consisting of questions on antimicrobial control at country, hospital and programme levels, was circulated to healthcare providers in the field of infectious diseases and microbiology through Asian Network for Surveillance of Resistant Pathogens, ReAct Group and the Australasian Society for infectious Diseases. Results: 139 participants from 16 countries or regions completed the survey. The majority of participants were adult infectious diseases physicians (61/139, 43.9%) and microbiologists (31/139, 22.3%). Participants from 7 countries reported that antimicrobials can be obtained without prescriptions. Despite the high percentage (75.5%) of respondents working in large hospitals, only 22/139 participants (15.8%) from Australia, China, Singapore, Taiwan, Thailand and Vietnam reported having more than 10 infectious diseases physicians. Hospital empiric antimicrobial guidelines for common infections were available according to 110/139 (79.1%) participants. Pre-authorisation of antimicrobials was reported by 88/113 (77.9%) respondents while prospective audit and feedback was reported by 93/114 (81.6%). Automatic stop orders and culture-guided de-escalation were reported by only 52/113 (46.0%) and 27/112 (24.1%) respectively. Conclusion: The survey reveals a wide range of ASP development in Asia Pacific. Establishing national workgroups and guidelines will help advance antimicrobial stewardship in this diverse region.